1993
DOI: 10.1128/jvi.67.10.5823-5832.1993
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hepatitis B virus expression and replication by hepatitis C virus core protein in HuH-7 cells

Abstract: Hepatitis B and C viruses (HBV and HCV, respectively) are associated with acute and chronic liver diseases and hepatocellular carcinoma. To elucidate the molecular status of superinfection with these two hepatitis viruses, we cotransfected the full-length or truncated version of HCV structural genes (core and envelope 1) together with the cloned HBV DNA into a human hepatoma cell line (HuH-7). Expression of HBV-specific major transcripts (3.5 and 2.1 kb), as well as HBV antigens (hepatitis B surface antigen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
123
2
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(135 citation statements)
references
References 68 publications
7
123
2
3
Order By: Relevance
“…8 In chronic HBV/HCV concurrent infection, it has been observed that HCV also exerts an inhibition on the expression of the HBV genome. [1][2][3][4]6,8 Our data showing that the patients in the case BC group and those in the control B group had a similar HBV viral load and similar dynamics of HBV-DNA negativization seem to refute an active inhibition of the chronic HCV infection on the acute HBV replication. This is suggested also by the observation that the HBV-DNA plasma values are similar in the case BC group and in the control B group at the different screening points.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…8 In chronic HBV/HCV concurrent infection, it has been observed that HCV also exerts an inhibition on the expression of the HBV genome. [1][2][3][4]6,8 Our data showing that the patients in the case BC group and those in the control B group had a similar HBV viral load and similar dynamics of HBV-DNA negativization seem to refute an active inhibition of the chronic HCV infection on the acute HBV replication. This is suggested also by the observation that the HBV-DNA plasma values are similar in the case BC group and in the control B group at the different screening points.…”
Section: Discussionmentioning
confidence: 66%
“…P atients with chronic hepatitis B virus (HBV)/hepatitis C virus (HCV) concurrent infection show a reciprocal inhibition of viral genomes, an association with a severe clinical presentation, and an infrequent response to interferon alfa treatment. [1][2][3][4][5][6][7][8][9][10] Instead, very lit-tle is known about HBV/HCV acute concurrent infection because only a few case reports are available in the literature. 11,12 Also, little is known about HBV acute infection when it develops in chronic HCV carriers, but the few case reports published on the topic suggest an association with a severe clinical presentation.…”
mentioning
confidence: 99%
“…These data concur with the in vitro demonstration by Shih et al that in the absence of host factors, the HCV-core protein can bind to HBV-RNA and suppress HBV gene expression and replication. 22 Using sequence comparison, Pontisso et al uphold this observation with the finding that the HBV core protein and the 101-102 core domain of HCV genotypes 1 and 3 share an important Arg-rich motif. 23 HBV replication would therefore be more effectively inhibited by HCV genotypes 1 and 3 than the remaining HCV genotypes, which do not share this homology with HBV.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, previous work suggests that HCV-mediated inhibition of HBV replication in patients coinfected with the two viruses most likely occurs through an HCV protein-mediated intracellular pathway (36). Studies in search of the HCV proteins that are responsible for the inhibition have reported that HCV core and NS2 proteins inhibited HBV replication in cultured cells, but so far, the underlined molecular mechanism(s) is not clear (9,12,38,43,44). Here we demonstrate that the HCV NS5A protein inhibits HBV gene transcription and DNA replication via the activation of the PI3K-Akt pathway and, thus may be, at least in part, responsible for the observed inhibition of HBV replication during HCV coinfection.…”
Section: Discussionmentioning
confidence: 99%